Stereotactic LINAC-Radiosurgery for Glomus Jugulare Tumors: A Long-Term Follow-Up of 27 Patients. - Faycal El Majdoub; Stefan Hunsche; Alhadi Igressa; Martin Kocher; Volker Sturm; Mohammad Maarouf (PLoS ONE, 2015)
The optimal treatment of glomus jugulare tumors (GJTs) remains controversial. Due to the critical location, microsurgery still provides high treatment-related morbidity and a decreased quality of life. Thus, we performed stereotactical radiosurgery (SRS) for the treatment of GJTs and evaluated the long-term outcome.Between 1991 and 2011, 32 patients with GJTs underwent SRS using a linear accelerator (LINAC) either as primary or salvage therapy. Twenty-seven patients (median age 59.9 years, range 28.7-79.9 years) with a follow-up greater than five years (median 11 years, range 5.3-22.1 years) were selected for retrospective analysis. The median therapeutic single dose applied to the tumor surface was 15 Gy (range 11-20 Gy) and the median tumor volume was 9.5 ml (range 2.8-51 ml).Following LINAC-SRS, 10 of 27 patients showed a significant improvement of their previous neurological complaints, whereas 12 patients remained unchanged. Five patients died during follow-up due to old age or other, not treatment-related reasons. MR-imaging showed a partial remission in 12 and a stable disease in 15 patients. No tumor progression was observed. The actuarial overall survival rates after five, ten and 20 years were 100%, 95.2% and 79.4%, respectively.Stereotactic LINAC-Radiosurgery can achieve an excellent long-term tumor control beside a low rate of morbidity in the treatment of GJTs. It should be considered as an alternative therapy regime to surgical resection or fractionated external beam radiation either as primary, adjuvant or salvage therapy.